Bhabinkamtibmas Strategy in Empowering Community Roles in Preventing Forest and Land Fires in Palangka Raya - Gregorius Herundo Martho; Yetrie Ludang; Bambang S. Lautt; Masliani Masliani (Eduvest - Journal of Universal Studies, 2024)
Bhabinkamtibmas strategy in an effort to create security and order by empowering community participation is expected to be able to prevent fire incidents which often occur throughout the year, administrative sanctions and civil sanctions, and alternative environmental dispute resolution which is not effective. The method used in this research is a combination of Quantitative and Qualitative using statistical analysis tools carried out in Palangka Raya, Jekan Raya District. The results of this research show that by using the PRA (Participatory Rural Appraisal) Test with the FGD method, the community supports and plays an active role in preventing forest and land fires. Apart from that, the results of the Variable Descriptive Statistical Analysis Test show all existing variables such as the Bhabinkamtibmas Strategy with a value of 17.039 > t table 1.992 and a significance value (Sig.) of 0.000 < 0.05, community role of 2.393 > t table 1.992 and significance value (Sig.) of 0.019 < 0.05 and community empowerment of 5.662 > t table 1.992 and significance value (Sig.) of 0.019 < 0.05 influential significantly towards preventing forest and land fires.